Comparative Genomic Analysis Reveals Genetic Variation and Adaptive Evolution in the Pathogenicity-Related Genes of Phytophthora capsici - Lee, Joung-Ho; Siddique, Muhammad Irfan; Kwon, Jin-Kyung; Kang, Byoung-Cheorl (Frontiers in Microbiology, 2021)
Phytophthora capsici is an oomycete pathogen responsible for damping off, root rot, fruit rot, and foliar blight in popular vegetable and legume crops. The existence of distinct virulence profiles and physiological races among the P. capsici population is a major constraint to developing resistant varieties of host crops. In the present study, we compared the genomes of three P. capsici isolates with different virulence profiles to reveal their genomic differences. We obtained genome sequences using short-read and long-read technologies, which yielded an average genome size of 76 Mbp comprising 514 contigs and 15,076 predicted genes. A comparative genomic analysis uncovered the signatures of accelerated evolution, gene family expansions in the pathogenicity-related genes among the three isolates. Resequencing two additional P. capsici isolates enabled the identification of average 1,023,437 SNPs, revealing the frequent accumulation of nonsynonymous substitutions in pathogenicity-related gene families. Furthermore, pathogenicity-related gene families, cytoplasmic effectors and ABC transporters, showed expansion signals in the more highly virulent isolates, with a greater number of nonsynonymous SNPs. This genomic information explains the plasticity, difference in virulence, and genome structural variation among the P. capsici isolates, providing insight into the genomic features related to the evolution and pathogenicity of this oomycete pathogen.